196 Effects of supplementing sow diets with fermented corn and soybean meal mixed feed during lactation on the performance of sows and progeny. (7th December 2018) - Wang, C; Shi, C; Lu, Z; Zhang, Y; Wang, Y
Abstract: In the present study, we studied the effects of feeding fermented corn and soybean meal mixed feed with Bacillus subtilis and Enterococcus faecium to lactating sows on the performance of the sows and their progeny. In Exp. 1, 60 sows were allocated to the following 3 dietary treatments: 1) sows fed a corn and soybean meal basal diet from d 3 before parturition to weaning, 2) a diet with 7.5% FMF, and 3) a diet with 15% FMF. Results indicated that feeding 15% FMF significantly improved (P < 005) the sows' ADFI, the individual piglet weight gain and reduced (P < 005) the backfat loss of sows compared with the control group. However, the 7.5% FMF treatment did not alter the performance of the sows or their progeny. Therefore, we considered the level of 15% FMF to be more efficient than 7.5% FMF. To verify the results of Exp. 1, we performed Exp. 2, in which 60 sows at 111 d of gestation were allocated into the following 2 dietary treatments: 1) sows fed a basal lactation diet from d 111 of gestation to weaning and 2) a basal diet with 15% FMF. Compared with the control group, 15% FMF inclusion increased (P < 005) the sows' ADFI and individual piglet weight gain during lactation and decreased the backfat loss of sows (P < 005) and piglet diarrhea incidence (P < 005). Additionally, the milk yield and IgA contents of the milk in sows fed 15% FMF were greater (P < 005) than those of the control group. Furthermore, the apparent total tract digestibility of sows was increased (P < 005) with 15% FMF supplementation. Therefore, the present study indicates that supplementing sow diets with 15% FMF during lactation has the potential to improve the performance of sows and progeny.